Residuals of organophosphate esters in foodstuffs and implication for human exposure. (February 2018) - Ding, Jinjian; Deng, Tongqing; Xu, Mengmeng; Wang, Shen; Yang, Fangxing
Abstract: Foodstuffs may be contaminated by organophosphate esters (OPEs) and become an important source of human exposure since OPEs are ubiquitous in the environment. In the present study, 10 OPEs were analyzed in various food matrices collected from a city in Eastern China including chicken, pork, fishes, vegetables, tofu, eggs, milk and cereals. The concentrations of Σ10 OPEs ranged from 1.1 to 9.6 ng g −1 fresh weight (fw) in the foodstuffs. Cereals had the highest residual level of total OPEs with a mean value of 5.7 ng g −1 fw. Tris(2-ethylhexyl) phosphate was detected in all foodstuff samples and showed the highest median residual concentration of 1.3 ng g −1 fw among the OPE analogs. The daily dietary intake of OPEs was calculated as 3.6 and 2.4 μg d −1 for adults and children. Cereals were identified as the major contributor to the total OPEs among different types of foodstuffs. Preliminary exposure assessment revealed that the current non-cancer health risks of OPEs via dietary intake were in the range of 10 −5 -10 −3, indicating low risk levels. Moreover, the hazard index of OPEs indicated that the risk for children (3 × 10 −3 ) was higher than adults (2 × 10 −3 ). Graphical abstract: Image 1 Highlights: Organophosphate esters were detected in foodstuffs from Eastern China. Cereals showed the highest residual level of OPEs. TEHP was the major OPE analog in foodstuffs. The risk is very low for residents exposed to OPEs through foodstuffs. The risk of OPEs for children was higher than adults. Abstract : The current risk is very low for residents exposed to OPEs by consumption of foodstuffs in Eastern China.